Teaching Technical Technical Vocabularyin Esp - Baxtiyarovna, Sadikova Makhbuba; Chorievna, Almardanova Zulfiya (PT. Antis International Publisher, 2024)
This article provides information on the use of dictionaries in the process of language learning and increasing vocabulary in technical universities. Today, there are a number of innovative ways to increase vocabulary. This article discusses ways to increase technical vocabulary with the help of dictionaries and its importance.